The Irish landscape in Somerville and Ross's fiction and illustrations, 1890-1915 - Stevens, Julie Anne (Trinity College (Dublin, Ireland). School of English, 2001)
As inheritors of an Anglo-Irish Protestant tradition who wrote in the midst of a vibrant consumer culture of the fin-de-siecle, Edith Somerville and Martin Ross developed their satirical fictions to reflect central ambiguities of Irish socio-political life. This study addresses both colonial contexts and aesthetic demands to recontextualize Somerville and Ross’s fiction and illustrations. It pays special attention to the writers’ involvement in a burlesque tradition, the influence of the British periodical industry’, and French art developments. It argues that the works’ parodic treatment of the myths and tropes of the Irish landscape depends not only- on the writers’ colonial inheritance but also on their modem sensibilities as expressed by the complex dynamic of Irish life during this period. The collaborative work from 1890 to 1915, when Martin Ross died, shows a development of form to express the multi-layered landscape of an Anglo-Irish inheritance. This work is divided into three sections: the colonial vision, which addresses the early novels, Naboth’s Vineyard and The Real Charlotte ; the magazine business, which contextualizes the short fiction; and the landscaping process, which concentrates on The Irish R.M. stories.
Keywords: Language and Literature. English, Ph.D.; Ph.D. Trinity College Dublin